Sound Effects. - Sacido-Romero, Jorge (DQR studies in literature., 2015)
Sound Effects collects original articles on English and American prose fiction which analyse vocal phenomena by using the psychoanalytic concept of the object voice - introduced by J. Lacan and theorised by M. Dolar - as their interpretative tool.